KOMUNIKASI PEMERINTAH DAN MASYARAKAT BERBASIS DIALEK BUDAYA LOKAL (Studi Kasus Proses Komunikasi Penunjang Pembangunan Berbasis Dialek Konjo pada Masyarakat di Tana Toa Kajang Kabupaten Bulukumba) - Syarifuddin Syarifuddin (BPSDMP Kominfo Jakarta, 2014)
ABSTRACTThis study deals with the phenomenon of communication process between the Government and the community using Konjo dialect (local dialect). Research also wants to get an overview about othat communication process through that language. By using qualitative research approach and methods of case study introduced by Yin, this reseacch shows that Konjo dialect is a form of verbal communication process without media in interpersonal and small group-communication settings. The participants who use Konjo dialect are local peoples, communities in Tana Toa Kajang Bulukumba. The communication process is bound with communication message called Pasang ri Kajang which mean